Directional Microphone Contralateral Routing of Signals in Cochlear Implant Users: A Within-Subjects Comparison. Issue 3 (May 2017) - Wimmer, Wilhelm; Kompis, Martin; Stieger, Christof; Caversaccio, Marco; Weder, Stefan
Abstract : Objectives: For medical or financial reasons, bilateral cochlear implantation is not always possible in bilaterally deafened patients. In such cases, a contralateral routing of signals (CROS) device could complement the monaural implant. The goal of our study was to compare the benefit of three different conditions: (1) unilateral cochlear implant (CI) alone, (2) unilateral CI complemented with a directional CROS microphone, and (3) bilateral CIs. Design: Twelve bilateral experienced CI users were tested. Speech reception in noise and sound localization were measured in the three above-mentioned conditions. Patients evaluated which condition they presumed to be activated and the subjective benefit on a hearing scale. Results: Compared with the unilateral CI condition, the additional CROS device provided significantly better speech intelligibility in noise when speech signals came from the front or side of the CROS microphone. Only small subjective improvement was observed. Bilateral-activated CIs further improved the hearing performance. This was the only condition where sound localization was possible. Subjective evaluation showed a clear preference for the bilateral CI treatment. Conclusions: In bilateral deafened patients, bilateral implantation is the most preferable form of treatment. However, patients with one implant only could benefit from an additional directional microphone CROS device. Abstract : Supplemental Digital Content is available in the text.